The Burden of Postoperative Delirium After Shoulder Arthroplasty and Modifiable Pharmacological Perioperative Risk Factors: A Retrospective Nationwide Cohort Study. Issue 1 (February 2023) - Kiani, Sara N.; Maron, Samuel Z.; Rao, Manasa G.; Zubizarreta, Nicole; Mazumdar, Madhu; Galatz, Leesa M.; Poeran, Jashvant; Cagle, Paul J.
Background: Increasing demand for shoulder arthroplasty and an aging population may increase the rate of complications associated with advanced age such as postoperative delirium, but little is known on its burden in this cohort. Purpose : We sought to answer the following questions: (1) What is the epidemiology of postoperative delirium after shoulder arthroplasty? (2) What modifiable risk factors can be identified for postoperative delirium after shoulder arthroplasty? (3) Do risk factors differ in those younger than and in those older than 70 years of age? Methods : In a retrospective nationwide cohort study, we extracted data from the Premier Healthcare database on inpatient total and reverse shoulder arthroplasties from 2006 to 2016. The primary outcome was postoperative delirium; modifiable risk factors of interest were perioperative opioid use (high, medium, or low), peripheral nerve block use, and perioperative prescription medications. Mixed-effects models assessed associations between risk factors and postoperative delirium. Odds ratios and confidence intervals are reported. We applied a cutoff of 70 years of age because it was the median age of the cohort, as well as the age at which we observed that delirium prevalence increased. Results : A total of 92, 429 total and reverse shoulder arthroplasties were identified (age range: 14–89 years). Overall delirium prevalence was 3.1% ( n = 2909). Age-specific prevalence of postoperative delirium was lower in patients aged 50 to 70 years and higher in those aged 70 years and older, up to 8% among those older than 88 years. After adjusting for relevant covariates, only long-acting and combined short-acting and long-acting benzodiazepines (compared with no benzodiazepines) were associated with increased odds of postoperative delirium. Corticosteroids were associated with decreased odds of postoperative delirium. Conclusion : Our retrospective cohort study demonstrated that benzodiazepine use and older patient age were significantly associated with postoperative delirium in shoulder arthroplasty patients. The relationship between benzodiazepine use and delirium was particularly notable among those 70 years of age and older. Further investigation is indicated, given the known adverse effects of benzodiazepines in older adults and our findings of higher than expected use of these medications in this surgical cohort.